Evaluation of the Antihyperglycemic and Antioxidant Potential of Hesperetin and Vitamin C as Adjuncts to Metformin in Streptozotocin-Induced Experimental Diabetes: Implications for Public Health and Community-Based Diabetes Prevention - Muhammad Atif, Asif Ur Rehman, Abdul Rehman Shahid, M. Gohar Ashraf Khan, Zubair Shahid, Malik Muhammad Kabir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia and increased oxidative stress, which contribute to the development of long-term complications. Conventional antidiabetic drugs such as Metformin effectively control blood glucose levels; however, additional therapeutic strategies targeting oxidative stress may enhance treatment outcomes. Natural antioxidants including Vitamin C and the citrus flavonoid Hesperetin have demonstrated potential antidiabetic and antioxidant properties in experimental studies. Objective: The present study aimed to evaluate the antidiabetic and antioxidant effects of hesperetin alone and in combination with vitamin C in metformin-treated Streptozotocin-induced diabetic rats and it's implications for public health and community base diabetes prevention. Methods: Experimental diabetes was induced in albino rats using streptozotocin. Animals were randomly divided into six groups including normal control, diabetic control, metformin-treated, metformin plus vitamin C, metformin plus hesperetin, and metformin combined with vitamin C and hesperetin. The treatment period lasted for 60 days. Fasting blood glucose, random blood glucose, glycated hemoglobin (HbA1c), and oxidative stress markers including malondialdehyde, glutathione, and superoxide dismutase were evaluated to assess glycemic control and antioxidant status. Results: Streptozotocin administration produced significant hyperglycemia and oxidative stress in diabetic rats. Treatment with metformin significantly reduced fasting and random blood glucose levels and improved HbA1c compared with the untreated diabetic group. The addition of vitamin C or hesperetin further improved glycemic parameters and antioxidant status. The combination therapy of metformin, vitamin C, and hesperetin demonstrated the most pronounced effects, showing substantial reductions in blood glucose, HbA1c, and malondialdehyde levels while enhancing glutathione and superoxide dismutase activity. Conclusion: The findings indicate that hesperetin and vitamin C enhance the antihyperglycemic and antioxidant effects of metformin in streptozotocin-induced diabetic rats. Combination therapy may represent a promising strategy for improving glycemic control and reducing oxidative stress associated with diabetes. Keywords: Diabetes mellitus, Metformin, Hesperetin, Vitamin C, Oxidative stress, Streptozotocin, Antioxidants.